Potensi Infusa Daun Paitan (Tithonia diversifolia) sebagai Larvasida Terhadap Mortalitas dan Morfologi Larva Aedes aegypti - Wahyuni, Dwi; Swandono, Hari Untarto; Purwani, Asih Imulda Hadi; Pramasari, Nadia; Putri, Sherlyna Rizkiya (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Dengue Hemorrhagic Fever is an infectious disease caused by the Dengue virus through the Aedes aegypti mosquito vector, which is controlled both at the larval and adult stages. The use of chemicals that are difficult to degrade in nature can pollute the environment. The Paitan plant (Tithonia diversifolia) contains secondary metabolite compounds that have the potential to be natural larvicides. This study aims to determine the natural larvicidal activity of Paitan leaf infusion. This study is an experimental study. The results of this study indicate that (1) Paitan leaf infusion contains alkaloid, flavonoid, terpenoid, saponin, phenolic, and tannin compounds. At concentrations of 1.8%, 3.2% and 5.6%, the mortality percentage results were 41.30%, 50.60% and 60% respectively; (2) The administration of Paitan leaf infusion has an effect on morphological damage Aedes aegypti larvae in the thorax, digestive tract and siphon. The content of different metabolite compounds causes different levels of morphological damage at each concentration